Steam-flaked corn diets containing combinations of wet corn gluten feed and alfalfa hay: effects on diet digestibility and ruminal characteristics - Sindt, J.J.; Montgomery, Sean P.; Pike, J.N.; Farran, T.B.; Coetzer, C.M.; Higgins, James J.; Drouillard, James S.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twelve ruminally cannulated Jersey steers were used to measure digestibility and ruminal characteristics of steam-flaked corn based diets containing combinations of wet corn gluten feed (WCGF) and alfalfa hay (AH). Starch intake was lower (P<0.05), but neutral detergent fiber intake was higher (P<0.05) as AH and WCGF increased in the diet. Ruminal pH was increased by AH (linear, P<0.05) and tended (P<0.07) to increase with WCGF. Feeding higher levels of WCGF tended to increase passage rate (P=0.17) and decreased (P<0.05) total tract organic matter digestibility. Flaked corn diets containing at least 25% WCGF may contribute enough roughage to allow reduction of alfalfa hay levels.
Keywords: Beef; Wet corn gluten feed; Steam-flaked corn; Digestibility